KESTABILAN PEWARISAN KARAKTER FENOTIP DAN PLOIDI Arachis hypogaea L. cv. Kelinci HASIL INDUKSI POLIPLOID - , HESTRI DYAH PUSPITASARI, Dr. Budi Setiadi Daryono, M.Agr.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Peanut (Arachis hypogaea L.) is one of the food commodity tha has high protein content. Nevertheless, in 2012 the productivity of peanut had reduction. Indonesia had to import an average 150.000 tons/year to fill the needed of peanut. Polyploid induction is one of the efforts should be made to improve the quality of peanut production. The polyploidy of peanut has superior characters than its diploid, such as has a higher stem height and number of leaves. One of the important parameter of plants polyploid induction product is phenotype characters stability. The purpose of this research was to study phenotype characters stability of filial (F1) peanut derived from polyploid induction. This research was done in four step. The research was started by planting, treatment, and observation of phenotype characters in KP4 UGM field. Measurement of phenotype characters included amount of leaves, length of plants, and production of pods and seed. Then, the chromosome ploidy was analyzed by using squashing method in Laboratory of Genetics in Faculty of Biology UGM and flow cytometry method in Laboratory of Plant Genetic, LIPI Cibinong. Nutrition of F1 was analyzed including of water content, total protein content, and crude fat content that was done in Laboratory of Food Technology in Faculty of Agriculture Technology UGM. Parameters data on this research were analyzed by using ANOVA statistic test and post hoc test of Tukey with SPSS 15 program. Result of this research showed that phenotype characters and ploidy of filial (F1) peanut cv. Kelinci were not stable. Similarly to control, the ploidy of F1 on this research was diploid.